A Bulky Chiral N‐Heterocyclic Carbene Nickel Catalyst Enables Enantioselective C−H Functionalizations of Indoles and Pyrroles. (3rd July 2019) - Diesel, Johannes; Grosheva, Daria; Kodama, Shota; Cramer, Nicolai
Abstract: An enantioselective nickel(0)‐catalyzed C−H functionalization of indoles and pyrroles that does not require the typical Lewis basic directing groups is disclosed. The reaction provides access to valuable tetrahydropyridoindoles and tetrahydroindolizines in high yields and enantioselectivity under mild reaction conditions. The process is characterized by a clear endo ‐cyclization preference to yield the sought‐after six‐membered‐ring products. Key for the success of the activation and selectivity in the cyclization was the development of a novel chiral SIPr carbene ligand analogue with very bulky flanking groups. Abstract : Gesicherte Flanken : Eine Ni 0 ‐katalysierte C‐H‐Funktionalisierung von Indolen, die ohne dirigierende Gruppen auskommt, liefert Tetrahydropyridoindole und Tetrahydroindolizine in hohen Ausbeuten und Enantioselektivitäten unter milden Bedingungen. Die Aktivierung und selektive Cyclisierung werden durch ein neuartiges chirales SIPr‐Carbenligand‐Analogon mit sehr sperrigen flankierenden Gruppen ermöglicht.